LANGUAGE VARIATIONS FOUND IN THE NOVEL BUMI MANUSIA BY PRAMOEDYA ANANTA TOER - Agus Sulaeman; Abdul Rohim; Zaenal Muttaqien (STIBA IEC JAKARTA, 2020)
The purpose of this study describes the use of language variations found in the novel Bumi Manusia by Pramoedya Ananta Toer. The approach used in this study is a qualitative approach and the method used is a content analysis method that aims to provide an objective picture of language variations in accordance with the data contained in the novel Bumi Manusia by Pramoedya Ananta Toer. The data used in this study are written data in the form of novel texts containing language variations in the novel Bumi Manusia by Pramoedya Ananta Toer published by Mardi Yuana Printing Graphic Printing in 2015. Based on the analysis, there are variations in language in the novel Bumi Manusia by Pramoedya Ananta Toer namely: Dutch, Japanese, Javanese and English. In the novel Bumi Manusia, Dutch is a variation of language that dominates from other languages ​​because in this novel it is told that there was a Dutchman in the Dutch East Indies. In the novel Bumi Manusia, Japanese is not very visible because Japanese is only a distraction in just one part. Javanese language can be said as a variation of language that dominates the two because in this novel tells the life of a genuine Javanese who falls in love with a Netherland. Same thing with the Javanese language in the novel Bumi Manusia, English is no less in existence with other language variations found in this novel. The significance of the study is to give useful information about the language variation and useful contribution for linguistic and education